Development of a Caregiver-Teacher Supported Physical Activity Program for Elementary School Students - Ünal, Fatma; Genç, Ayça; Dünya, Beyza Aksu; Durak, Hatice Yıldız; Büyükşahin, Yasemin; Büyükşahin, Yasemin; Ünal, Fatma; Dünya, Beyza Aksu; Genç, Ayça (My University, 2025)
Childhood obesity has been a significant concern worldwide. According to World Health Organization data the pandemic, pose a danger to the world between March 2020 and May 2023, has deepened this concern given the restriction measures such as closures taken to avoid the spread. Following the pandemic, a gap in the literature has arisen concerning the assessment of the long-term impact and potential side effects of physical activity restrictions on children. This study aims to address this gap by developing a comprehensive, needs-based physical activity school program and a web application for home settings, specifically designed for elementary schoolers in Türkiye. To gather essential information on the needs and current status of children in terms of physical and emotional well-being, as well as motor skills and physical activity habits from the perspectives of their caregivers, a thorough needs analysis study was conducted. This study used surveys. 27 volunteer parents participated in the study. The data were analyzed using content analysis. With these findings, an individual activity program consisting of different components was developed, taking into account the development levels and physical fitness levels of elementary school students. Individualized physical activity programs developed within this framework were created taking into account the individual needs and abilities of students and in order to support these needs, and were planned in two separate structures to be implemented with teachers at school and with parents at home.
Keywords: Physical activity; Physical education and sport; Educational games